2020
DOI: 10.1111/bjh.16474
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance therapy with ex vivo expanded lymphokine‐activated killer cells and rituximab in patients with follicular lymphoma is safe and may delay disease progression

Abstract: Summary Anti‐cluster of differentiation 20 (CD20) monoclonal antibodies (mAbs) have shown promise in follicular lymphoma (FL) as post‐induction therapy, by enhancing antibody‐dependent cellular cytotoxicity (ADCC). However, cytotoxic cells are reduced after this treatment. We hypothesised that ex vivo expanded lymphokine‐activated killer (LAK) cells administered to FL‐remission patients are safe and improve anti‐CD20 efficacy. This open, prospective, phase II, single‐arm study assessed safety and efficacy of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Antibody-based therapy has become a critical part of the treatment landscape in hematologic malignancies in the past few decades and several monoclonal In patients with DLBCL and follicular lymphoma treated with anti-CD20 monoclonal antibodies, low pre-treatment NK cell count was associated with shorter progression free survival and decreased overall survival compared to patients with higher pre-treatment NK cells [45]. NK cell ADCC has been exploited in antibody therapy by systemic cytokine stimulation of endogenous NK cells [46][47][48][49][50] or in combination with adoptive NK cell therapy [43,51]. Autologous cytokine-expanded NK cells were combined with chemotherapy and rituximab in 9 patients with relapsed CD20positive lymphoma patients to enhance ADCC [43].…”
Section: Targeting Nk Cells To Nhl With Antibodiesmentioning
confidence: 99%
“…Antibody-based therapy has become a critical part of the treatment landscape in hematologic malignancies in the past few decades and several monoclonal In patients with DLBCL and follicular lymphoma treated with anti-CD20 monoclonal antibodies, low pre-treatment NK cell count was associated with shorter progression free survival and decreased overall survival compared to patients with higher pre-treatment NK cells [45]. NK cell ADCC has been exploited in antibody therapy by systemic cytokine stimulation of endogenous NK cells [46][47][48][49][50] or in combination with adoptive NK cell therapy [43,51]. Autologous cytokine-expanded NK cells were combined with chemotherapy and rituximab in 9 patients with relapsed CD20positive lymphoma patients to enhance ADCC [43].…”
Section: Targeting Nk Cells To Nhl With Antibodiesmentioning
confidence: 99%
“…Based on the findings of these studies, concurrent treatment with chemotherapy and activated lymphocyte therapy could be preferred to activated lymphocyte therapy alone; however further controlled studies are required to clarify the efficacy of activated lymphocyte therapy for feline LGLL. Moreover, the potential toxicity and safety issues of the activated lymphocyte therapy make the use of this therapy controversial, although some reports have described that this therapy is safe in cats and other species ( Takayama et al ., 2000 ; Hoshino et al ., 2008 ; O’Connor et al ., 2012 ; Maeta et al ., 2019 ; López-Díaz de Cerio et al ., 2020 ; Gareau et al ., 2021 ; Mitani et al ., 2021 ). In a human randomized trial, compared with surgical resection alone, activated lymphocyte therapy after surgical resection of hepatocellular carcinoma decreased the frequency of recurrence, prolonged the time to first recurrence, improved the recurrence-free survival, and improved the disease-specific survival ( Takayama et al ., 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…This therapy is generally administered in combination with chemotherapy in veterinary medicine ( O’Connor and Wilson-Robles, 2014 ; Bujak et al ., 2018 ). In human and canine cancer patients, concurrent treatment with activated lymphocyte therapy and chemotherapy decreased recurrence risk, improved the quality of life (QOL), or prolonged survival time without serious adverse events ( Takayama et al ., 2000 ; O’Connor et al ., 2012 , 2013 ; López-Díaz de Cerio et al ., 2020 ; Mitani et al ., 2021 ). Furthermore, activated lymphocyte therapy was reported to be safe and feasible for postoperative QOL maintenance in older feline cancer patients ( Maeta et al ., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among the immunotherapy methods being considered for anticancer therapy, adoptive transfer of lymphokine-activated killer (LAK) cells is one of the biotherapy approaches that has been translated into clinical studies [1][2][3][4][5]. In vitro culture of peripheral blood mononuclear cells (PBMCs) with interleukin-2 (IL-2) for several days results in a population of LAK cells with upregulated cytotoxicity against cancer cells and IFN-γ production [6].…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical trials have successfully activated and expanded LAK cells using IL-2 [1,2,7,[10][11][12]. When LAK cells were first introduced by Rosenberg et al in 1985 [10,11], eleven of 25 patients showed significant cancer reduction, with one showing complete tumor regression.…”
Section: Introductionmentioning
confidence: 99%